Automated Urban Drinking Water Suppy Control and Water Theft Identification System - SWETHA JOSHI, SWETHA S, YASHASWINI N and SWATHI R (2011)
INTERNAL GUIDE: KRISHMOORTHY M, ECE DEPT, MVJCE
Keywords: Automated Urban Drinking Water Suppy Control and Water Theft Identification System